Genetic engineering of Saccharomyces Cerevisiae for the efficient synthesis and secretion of proteolytic enzymes - Lourens, Karien,1970- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1995.